Elements of nature - Shaughnessy, Jonathan; Théberge, Pierre; Graham, Mayo (Ottawa : National Gallery of Canada Ottawa, 2005)
Xian, Ah ; Dean, Tacita ; Ewen, Paterson ; Goldstein, Jack ; Honert, Martin ; Ipeelee, Osuitok ; Magor, Liz ; Merz, Mario ; Penone, Giuseppe ; Saumik, Bernadette Ivalooarjuk ; Snow, Michael ; Tungilik, Marc ; Whittome, Irène F.
biog. p. 89-92
Engels
Exhibition. Elements of nature. Cité de l'énergie Shawinigan. National Gallery of Canada Ottawa. 11.06.2005 - 02.10.2005
boek